The intractable cigarette 'filter problem'. (18th April 2011) - Harris, Bradford
Abstract : Background: When lung cancer fears emerged in the 1950s, cigarette companies initiated a shift in cigarette design from unfiltered to filtered cigarettes. Both the ineffectiveness of cigarette filters and the tobacco industry's misleading marketing of the benefits of filtered cigarettes have been well documented. However, during the 1950s and 1960s, American cigarette companies spent millions of dollars to solve what the industry identified as the 'filter problem'. These extensive filter research and development efforts suggest a phase of genuine optimism among cigarette designers that cigarette filters could be engineered to mitigate the health hazards of smoking. Objective: This paper explores the early history of cigarette filter research and development in order to elucidate why and when seemingly sincere filter engineering efforts devolved into manipulations in cigarette design to sustain cigarette marketing and mitigate consumers' concerns about the health consequences of smoking. Methods: Relevant word and phrase searches were conducted in the Legacy Tobacco Documents Library online database, Google Patents, and media and medical databases including ProQuest, JSTOR, Medline and PubMed. Results: 13 tobacco industry documents were identified that track prominent developments involved in what the industry referred to as the 'filter problem'. These reveal a period of intense focus on the 'filter problem' that persisted from the mid-1950s to the mid-1960s, featuring collaborations between cigarette producers and large American chemical and textile companies to develop effective filters. In addition, the documents reveal how cigarette filter researchers' growing scientific knowledge of smoke chemistry led to increasing recognition that filters were unlikely to offer significant health protection. One of the primary concerns of cigarette producers was to design cigarette filters that could be economically incorporated into the massive scale of cigarette production. The synthetic plastic cellulose acetate became the fundamental cigarette filter material. By the mid-1960s, the meaning of the phrase 'filter problem' changed, such that the effort to develop effective filters became a campaign to market cigarette designs that would sustain the myth of cigarette filter efficacy. Conclusions: This study indicates that cigarette designers at Philip Morris, British-American Tobacco, Lorillard and other companies believed for a time that they might be able to reduce some of the most dangerous substances in mainstream smoke through advanced engineering of filter tips. In their attempts to accomplish this, they developed the now ubiquitous cellulose acetate cigarette filter. By the mid-1960s cigarette designers realised that the intractability of the 'filter problem' derived from a simple fact: that which is harmful in mainstream smoke and that which provides the smoker with 'satisfaction' are essentially one and the same. Only in the wake of this realisation did the agenda of cigarette designers appear to transition away from mitigating the health hazards of smoking and towards the perpetuation of the notion that cigarette filters are effective in reducing these hazards. Filters became a marketing tool, designed to keep and recruit smokers as consumers of these hazardous products.